Fluid-structure interaction analysis of the left coronary artery with variable branch angulation - Dong, J.; Sun, Zhonghua; Inthavong, K.; Tu, J. (Taylor & Francis, 2014)
The aim of this study is to elucidate the correlation between coronary artery branch angulation, local mechanical and haemodynamic forces at the vicinity of bifurcation. Using a coupled fluid–structure interaction (FSI) modelling approach, five idealized left coronary artery models with various angles ranging from 708 to 1108 were developed to investigate the influence of branch angulations. In addition, one CT image-based model was reconstructed to further demonstrate the medical application potential of the proposed FSI coupling method. The results show that the angulation strongly alters its mechanical stress distribution, and the instantaneous wall shear stress distributions are substantially moderated by the arterial wall compliance. As high tensile stress is hypothesized to cause stenosis, the left circumflex side bifurcation shoulder is indicated to induce atherosclerotic changes with a high tendency for wide-angled models.